EPIGAEIC ANTS IN A FOREST REMNANT IN THE STATE OF ACRE, BRAZIL AND NEW RECORDS FOR THE STATE - Santos, Rodrigo Souza; Delabie, Jacques Hubert Charles (REVISTA DE AGRICULTURA, 2018)
Ants are considered an important group of invertebrates in terrestrial ecosystems, where they participate in important ecological processes between animals and plants, and they are considered good indicators of environmental impacts as well. Although the diversity of ants in the Amazon biome is already relatively well known, the ant fauna in the state of Acre, Brazil is still poorly known. The aim of this study was to carry out a survey of ants in a forest remnant located in the municipality of PlÃ¡cido de Castro, Acre, using pitfall traps. Thirty-six species of ants were collected from six subfamilies and 18 genera. Of the species confirmed, 11 (Cephalotes serraticeps, Gnamptogenys moelleri, Gnamptogenys triangularis, Neoponera apicalis, Neoponera commutata, Neoponera verenae, Mayaponera constricta, Megalomyrmex emeryi, Pachycondyla impressa, Pheidole araneoides, and Odontomachus caelatus) were first records for Acre, increasing our knowledge of the epigaeic ants that occur in this region of the Amazon.